How Cost-Benefit Evaluations and Stigmatization Influence Individuals’ Acceptance of Medical Interventions for Severe Obesity (The Journal of Medicine, Humanity and Media, 2025)
Obesity has become a global epidemic, and the Chinese government has launched the “Weight Management Year” program in 2025. Besides traditional methods (e.g., balanced dieting and regular exercise), medical interventions (e.g., weight loss surgery and medications) also serve as alternatives for overweight people to lose weight. But medical interventions to lose weight have been socially stigmatized on social media, which might discourage individuals from receiving medical treatments. This study investigated how five factors, including self-efficacy, outcome expectancy, perceived severity of type-2 diabetes, perceived safety concern of semaglutide, and perceived stigma of semaglutide, influence individuals’ attitudes towards medical interventions for weight loss purposes and whether they would recommend semaglutide to others from a cost-benefit perspective. According to the result of the hierarchical regressional model based on an online survey (N = 397), only outcome expectancy and perceived stigma of semaglutide significantly influence the willingness to recommend. This means that health educators should raise the public’s awareness of the potential harm of obesity and normalize the use of medical treatments for weight loss purposes.
Keywords: Weight management; Semaglutide; Social cognitive theory; Stigmatization